(untitled) (Journal of the College of Basic Education, 2023)
Agricultural development in Maysan Governorate is affected by a group of elements resulting from natural and human geographical factors that in turn affected their spatial distribution on this activity in the study area. Congruence of the factors affecting agricultural development, and conducting these operations to address the problems facing agricultural development and increasing the amount of production in the governorate, and they are as follows: